Perancangan Website sebagai Media Informasi Asuransi Kendaraan PT. RODA INSURANCE - Elkana, Elkana Berutu; Fadhil, Fadhil Ihsan; Fajri, Fajri Fatila; Ramya, Ramya Harfi; Eka, Eka Kusuma Pratma (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
In the digital era, PT. Roda Insurance recognizes the significance of information technology in enhancing operational efficiency and customer service. This research explores system analysis, design, implementation, and performance evaluation to bridge the gap between vehicle insurance providers and customers. The findings indicate that the adoption of information technology can significantly improve business process efficiency and the quality of services provided to clients. Consequently, information technology not only facilitates internal management but also strengthens clients' trust in the company.